2020
DOI: 10.4097/kja.20323
|View full text |Cite
|
Sign up to set email alerts
|

The role of regional analgesia in personalized postoperative pain management

Abstract: Pain management plays a fundamental role in enhanced recovery after surgery pathways. The concept of multimodal analgesia in providing a balanced and effective approach to perioperative pain management is widely accepted and practiced, with regional anesthesia playing a pivotal role. Nerve block techniques can be utilized to achieve the goals of enhanced recovery, whether it be the resolution of ileus or time to mobilization. However, the recent expansion in the number and types of nerve block approaches can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 57 publications
0
33
0
2
Order By: Relevance
“…The increased postoperative day 1 opioid use may be reflective of poorly controlled acute postoperative pain, a known risk factor for developing persistent pain after various surgical procedures 19–22. For this reason, literature strongly supports the use of multimodal analgesia, early counseling, peripheral nerve blocks as well as neuraxial anesthesia as strategies to minimize the transition from acute to prolonged opioid requirement after surgery 23–25…”
Section: Discussionmentioning
confidence: 99%
“…The increased postoperative day 1 opioid use may be reflective of poorly controlled acute postoperative pain, a known risk factor for developing persistent pain after various surgical procedures 19–22. For this reason, literature strongly supports the use of multimodal analgesia, early counseling, peripheral nerve blocks as well as neuraxial anesthesia as strategies to minimize the transition from acute to prolonged opioid requirement after surgery 23–25…”
Section: Discussionmentioning
confidence: 99%
“…The key strategy to enhance perioperative pain management includes the use of a multimodal analgesia approach to reduce opioid consumption, decrease time in the hospital and improve patient satisfaction [ 2 ]. Ultrasound-guided nerve block has become a crucial component of the multimodal analgesia approach [ 3 ]. A large number of studies have shown that the perioperative analgesic effect of nerve block is superior to that of other drugs [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regional analgesia uses different nerve block techniques as part of the multimodal analgesia arsenal to favor ERAS. 28 Techniques are presented in two different chronologic groups: 1) Classic Techniques; and 2) Novel Techniques.…”
Section: Regional Analgesia For Tkamentioning
confidence: 99%